Efficacy of Humanized Exposures of Cefiderocol (S-649266) against a Diverse Population of Gram-Negative Bacteria in a Murine Thigh Infection Model - Monogue, Marguerite L. (Antimicrob Agents Chemother, 2017)
Cefiderocol (S-649266) is a novel siderophore cephalosporin with potent in vitro activity against clinically encountered multidrug-resistant (MDR) Gram-negative isolates; however, its spectrum of antibacterial activity against these difficult-to-treat isolates remains to be fully explored in vivo. Here, we evaluated the efficacy of cefiderocol humanized exposures in a neutropenic murine thigh model to support a suitable MIC breakpoint. Furthermore, we compared cefiderocol's efficacy with humanized exposures of meropenem and cefepime against a subset of these phenotypically diverse isolates. Ninety-five Gram-negative isolates were studied. Efficacy was determined as the change in log(10) CFU at 24 h compared with 0-h controls. Bacterial stasis or ≥1 log reduction in 67 isolates with MICs of ≤4 μg/ml was noted in 77, 88, and 85% of Enterobacteriaceae, Acinetobacter baumannii, and Pseudomonas aeruginosa, respectively. For isolates with MICs of ≥8 μg/ml, bacterial stasis or ≥1 log(10) reduction was observed in only 2 of 28 (8 Enterobacteriaceae, 19 A. baumannii, and 1 P. aeruginosa) strains. Against highly resistant meropenem and cefepime organisms, cefiderocol maintained its in vivo efficacy. Overall, humanized exposures of cefiderocol produced similar reductions in bacterial density for organisms with MICs of ≤4 μg/ml, whereas isolates with MICs of ≥8 μg/ml generally displayed bacterial growth in the presence of the compound. Data derived in the current study will assist with the delineation of MIC susceptibility breakpoints for cefiderocol against these important nosocomial Gram-negative pathogens; however, additional clinical data are required to substantiate these observations.